Laparoscopic Treatment of Intrauterine Fallopian Tube Incarceration. (28th April 2013) - Kondo, William; Bruns, Rafael Frederico; Nicola, Marcelo Chemin; Ribeiro, Reitan; Trippia, Carlos Henrique; Zomer, Monica Tessmann
Abstract : Herniation of the pelvic structures into the uterine cavity (appendix vermiformis, small bowel, omentum, or fallopian tube) may occur after uterine perforation. In this paper, we describe one case of intrauterine fallopian tube incarceration treated by means of laparoscopic surgery.